An investigation of media usage purposes and social media addiction levels of faculty of sport sciences students - Recep Nur Uzun; Bade Yamak; Serhat Erail; Özge Orhan Akar (ROL Spor Bilimleri Dergisi, 2025)
The aim of this study is to examine the media usage purposes and social media addiction levels of students in Faculties of Sport Sciences. The study was conducted using a quantitative research design based on the descriptive survey model. An online questionnaire was administered to a total of 900 students (486 female, 414 male) enrolled in various Sport Sciences faculties. The data collection tools included a "Personal Information Form", the "Media Usage Purposes Scale" and the "Social Media Addiction Scale". Independent Samples T-Test was used to analyze the data. Group comparisons were made based on variables such as gender, department, year of study, type of social media platform used, and duration of use. According to the findings, there were no statistically significant differences in students' media usage purposes based on gender, class level, or type of social media platform (p>0.05); however, male students in the Recreation department had significantly higher social media addiction scores compared to their female counterparts (p<0.05). No other significant differences were found among the remaining departments and variables (p>0.05). Although a slight increase in addiction scores was observed with longer social media use, this increase was not statistically significant. When compared with the existing literature, the findings are generally consistent with previous studies and indicate that social media addiction is shaped by individual and contextual factors. In conclusion, media usage among sport sciences students is highly prevalent; however, the level at which this usage turns into addiction appears to be limited. The study aims to provide recommendations that may help students manage their relationship with digital media in a more conscious and controlled manner.